Preparation method of waterproof multi-component composite fabric

Through the combination of modified polyacrylonitrile and expanded graphite-hydrotalcite, combined with electrostatic spraying, the modified polyurethane is deposited to form a protective layer with wrinkled microsphere structure, which solves the problem of mutual repulsion of multi-component composite fabrics during the composite process, and achieves the multifunctional effect of high strength, waterproof, antibacterial, hygroscopic and heat-absorbing.

CN119824691APending Publication Date: 2025-04-15JIANGSU PEIPU POLYMER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411768706.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing multi-component composite fabrics may have problems of mutual repulsion and affecting performance during the composite process, and existing antibacterial agents are prone to failure after encountering water, making it difficult to achieve long-term antibacterial effects.

Method used

The combination of modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder is formed, and the modified polyurethane is deposited on the surface of the fabric by electrostatic spraying to form a protective layer with wrinkled microsphere structure, enhancing waterproof performance, and chemically bonding active groups to the surface of the fabric to form a stable protective layer, optimizing the elastic and mechanical properties of the polyurethane.

Benefits of technology

It achieves multi-functional effects of high strength, waterproof, antibacterial, hygroscopic and heat absorption, enhances the mechanical properties and waterproof properties of the fabric, and reduces the aging phenomenon caused by copper ion oxidation, achieving a long-term antibacterial effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005169678400000081
    Figure BDA0005169678400000081
Patent Text Reader

Abstract

The invention discloses a preparation method of a waterproof multi-component composite fabric, and relates to the technical field of composite fabrics. The preparation method comprises the following steps: firstly, preparing modified polyurethane carrying a silane chain segment from 2-butene-1, 4-diol, 1-chloromethyl-2, 4-dicyanobenzene and 1, 3-bis (3-aminopropyl)-1, 1, 3, 3-tetramethyldisiloxane, and depositing the modified polyurethane on the surface of the moisture-absorbing and heat-generating fabric by utilizing an electrostatic spraying method to form a firm protective layer; the elasticity and the mechanical property of the polyurethane protection layer are optimized; and finally, jointly hot-pressing to form the waterproof multi-component composite fabric. According to the moisture absorption and heating fabric, 4-(1-amino-3-methylsulfonyl-propyl)-1, 6-heptadiene-4-alcohol participates in a polyacrylonitrile polymerization reaction, a cross-linked net structure is formed, and the mechanical strength and the antibacterial performance of the fabric are remarkably improved; then coordination binding with copper chloride is carried out, so that the antibacterial effect is improved; and then melting and spinning with an expanded graphite-hydrotalcite mixture to prepare honeycomb microporous structure fibers, so that the tensile strength and hygroscopicity of the fibers are enhanced, and a heating effect is generated through moisture absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite fabrics, and in particular to a method for preparing a waterproof multi-component composite fabric. Background Art

[0002] In cold environments, people have a strong demand for fabrics that can actively generate heat. Traditional thermal insulation fabrics mainly rely on preventing heat dissipation to keep warm, such as down and wool fabrics in down jackets. Their thermal insulation principle is to form an insulation layer by filling air or their own fiber structure. However, the thermal insulation effect of these fabrics will be greatly reduced in a humid environment, and they cannot actively generate heat. Therefore, hygroscopic and heat-generating fabrics came into being. They can absorb water vapor emitted by the human body and convert it into heat. While providing warmth, they can also keep the skin surface dry. However, excessive water vapor can lead to the growth of bacteria. At present, the realization of antibacterial fabrics is mainly achieved by adding organic antibacterial agents or inorganic antibacterial agents during finishing. The method of adding antibacterial agents includes using them during the fabric finishing process. These antibacterial agents can be attached to the fiber surface by chemical bonding, physical adsorption, etc., thereby inhibiting the growth of bacteria, and the antibacterial effect of the later finishing has the problem of being easily ineffective after contact with water.

[0003] Multi-component fabrics are designed to achieve synergistic effects of multiple functions through the combination of different materials or fibers. However, the research and development of multi-component composite fabrics faces many technical challenges. Hygroscopic and heat-generating fibers, antibacterial fibers, and waterproof fibers or materials may repel each other and affect each other's performance during the composite process. The second is the complexity of the preparation process. To integrate multiple functions into one fabric, it is necessary to precisely control the proportion, distribution, and combination of each component. Therefore, it is very important to invent a composite fabric with multiple functions such as hygroscopic and heat-generating, antibacterial, and waterproof. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a waterproof multi-component composite fabric to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a waterproof multi-component composite fabric, comprising the following preparation steps:

[0006] (1) 5 to 15 parts of modified polyacrylonitrile and 60 to 180 parts of toluene are uniformly mixed, 1 to 3 parts of copper chloride-ethanol solution are added, and the mixture is stirred at 180 rpm for 40 to 60 minutes. The solid is collected and placed in an oven at 50 to 60° C. to dry for 14 to 18 hours to obtain a composite modified polyacrylonitrile;

[0007] (2) drying the composite modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder at 80-100° C. for 1-2 hours, transferring it into a spinning machine for melt spinning at 330-340° C., then drawing it to 0.7-2.5 times at 280-290° C., curling it at 260-280° C., relaxing and shaping it at 255-285° C., drawing it to 0.6-1.2 times, cooling it at a temperature of 14-22° C., a wind speed of 0.6-1.2 m / s, and a wind pressure of 600-800 Pa, cooling it for 10-20 minutes, and weaving it into a fabric by warp and weft interlacing to obtain a moisture-absorbing and heat-generating fabric;

[0008] (3) Under a nitrogen atmosphere, 6 to 14 parts of 2-butene-1,4-diol and 48 to 106 parts of dimethylformamide were mixed uniformly at 70 to 80° C., 4 to 10 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.1 to 0.3 parts of dibutyltin dilaurate were added, and the mixture was reacted at 120 rpm for 2 to 6 hours, and the temperature was lowered to 25 to 35° C., and 5 to 11 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added dropwise at a rate of 1 mL / min, and the mixture was reacted for 1 to 3 hours. The solid was collected by filtration, washed with deionized water for 3 times, and dried in an oven at 55 to 65° C. for 10 to 16 hours to obtain a modified polyurethane;

[0009] (4) 13 to 31 parts of modified polyurethane, 100 to 240 parts of dimethylformamide, and 25 to 55 parts of tetrahydrofuran are stirred at 30°C for 1 to 2 hours, and then conveyed to an electrostatic spray assembly via a metering pump and sprayed onto the surface of a hygroscopic and heat-generating fabric 15 cm away from the nozzle. The fabric is then heat-pressed with a heat press for 2 to 4 minutes to obtain a waterproof multi-component composite fabric.

[0010] Furthermore, the preparation step of the modified polyacrylonitrile in step (1) is as follows: under a nitrogen atmosphere, 3 to 7 parts of 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol, 15 to 25 parts of acrylonitrile, 0.1 to 0.3 parts of azobisisobutyronitrile, and 75 to 125 parts of dimethyl sulfoxide are mixed uniformly, the temperature is raised to 55 to 65° C., and the mixture is stirred at 100 rpm for 10 to 16 hours. 250 to 400 parts of methanol are added, and the mixture is stirred for 25 to 45 minutes. The solid is filtered and washed with methanol for 3 times, and dried in an oven at 50 to 60° C. for 14 to 18 hours to obtain the modified polyacrylonitrile.

[0011] Furthermore, the content of copper chloride in the copper chloride-ethanol solution in step (1) is 0.1 g / mL.

[0012] Furthermore, in step (2), the mass ratio of the composite modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder is 20:1.

[0013] Furthermore, in the expanded graphite-hydrotalcite mixed powder of step (2), the ratio of expanded graphite to hydrotalcite is 1:2.

[0014] Furthermore, the parameters of the spinning machine in step (2) are: spinning pressure 40-60 MPa, humidity 48-60%, and spinning speed 1200 m / min.

[0015] Furthermore, the cooling rate in step (3) is 5°C / min.

[0016] Furthermore, the parameters of the electrostatic spray assembly in step (4) are a voltage of 10 to 20 kV and an injection speed of 0.5 to 0.9 mL / h.

[0017] Furthermore, the temperature of the hot press in step (4) is 170°C.

[0018] Furthermore, the pressure of the hot press in step (4) is 1 to 5 MPa.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0020] The invention combines the hydroxyl group of 2-butene-1,4-diol with the isocyanate group in 1-chloromethyl-2,4-diisocyanobenzene, and modifies it with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to prepare a modified polyurethane carrying a silane segment. The modified polyurethane is deposited on the surface of a hygroscopic and heat-generating fabric by an electrostatic spray method. Under the action of an electric field force, the modified polyurethane breaks through the surface tension in the form of droplets. When flying in the air, the solvent in the droplets evaporates to form a wrinkled microsphere structure, thereby improving the liquid repellency and further enhancing the waterproof performance. The active groups in the droplets can react with the hygroscopic and heat-generating fabric under the action of electrostatic force. The surface of the fabric is bonded by chemical bonds to form a stable and firm protective layer on the surface of the fabric. The presence of silane chain segments can optimize the elasticity and mechanical properties of the polyurethane protective layer, thereby indirectly improving the mechanical properties of the fabric. At the same time, it reduces the phenomenon of fabric aging caused by oxidation of copper ions in the hygroscopic and heat-generating fabric, thereby achieving a long-lasting antibacterial effect. The protective layer carries multiple hydrophobic groups such as benzene rings, alkyl chains, and silicon-oxygen bonds, which can initially isolate bacterial adhesion, which is beneficial to the improvement of the antibacterial effect and can also achieve the waterproof effect of the fabric. Finally, they are hot-pressed together to form a waterproof multi-component composite fabric to achieve high strength, waterproof, antibacterial, hygroscopic and heat-generating effects.

[0021] Among them, the hygroscopic and heat-generating fabric first participates in the polymerization reaction of polyacrylonitrile through 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol to form a cross-linked network structure, which significantly improves the mechanical strength of the fabric, assists the sulfur element, and further improves the antibacterial performance. At the same time, the presence of hydroxyl can improve the hydrophilicity of the fabric, thereby enhancing the hygroscopic effect; then through the coordination and combination of amino groups and copper chloride, copper ions can destroy the outer cell membrane of bacteria, disrupt the internal current of bacteria, and hinder bacterial regeneration, thereby achieving the antibacterial effect; then melt-spun with the expanded graphite-hydrotalcite mixture to form the fabric, the expanded graphite-hydrotalcite mixture can gather and compress trace gases, so that the fiber has a honeycomb microporous structure, increase the specific surface area of ​​the fiber, thereby enhancing the capillary action of the fiber and improving the hygroscopicity. At the same time, the enhancement of hygroscopicity enables the fiber to absorb water molecules in the air, converting it from gas to liquid, liquefying to generate heat, thereby achieving the heating effect. On this basis, there are many irregular pores in the honeycomb structure, which increases the extensibility of the fiber and improves the tensile strength of the fiber. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the waterproof multi-component composite fabrics prepared in the following examples.

[0024] Tensile strength: The same size of the embodiment and the comparative example were tested according to the standard GB / T 3923.1-1997.

[0025] Antibacterial rate: Take the embodiment and the comparative example of the same size and test them according to the standard GB / T 20944.3.

[0026] Hygroscopic heat rise temperature: Take the embodiment and comparative example of the same size and test them according to the standard GB / T 29866-2013.

[0027] Waterproofness: Take the embodiment and comparative example of the same size, with the polyurethane layer on the front, and test according to the standard AATCC-22-2017.

[0028] Example 1: (1) Under a nitrogen atmosphere, 3 parts of 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol, 15 parts of acrylonitrile, 0.1 parts of azobisisobutyronitrile, and 75 parts of dimethyl sulfoxide were mixed uniformly, heated to 55°C, stirred at 100 rpm for 10 h, 250 parts of methanol were added, stirred for 25 min, the solid was filtered, washed with methanol 3 times, and dried in an oven at 50°C for 14 h to obtain modified polyacrylonitrile;

[0029] (2) 5 parts of modified polyacrylonitrile and 60 parts of toluene were mixed evenly, 1 part of a copper chloride-ethanol solution having a copper chloride content of 0.1 g / mL was added, and the mixture was stirred at 180 rpm for 40 min. The solid was collected and placed in an oven at 50° C. to dry for 14 h to obtain a composite modified polyacrylonitrile;

[0030] (3) The composite modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder were dried at 80°C for 1 hour, transferred into a spinning machine and melt-spun at 330°C, wherein the spinning pressure was 40MPa, the humidity was 48%, and the spinning speed was 1200m / min, then stretched to 0.7 times at 280°C, curled at 260°C, relaxed and shaped at 255°C, stretched to 0.6 times, cooled at a cooling air temperature of 14°C, a wind speed of 0.6m / s, and a wind pressure of 600Pa, cooled for 10 minutes, and woven into a fabric by warp and weft interlacing to obtain a hygroscopic and heat-generating fabric; the mass ratio of the composite modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder was 20:1; the ratio of expanded graphite to hydrotalcite in the expanded graphite-hydrotalcite mixed powder was 1:2;

[0031] (4) Under a nitrogen atmosphere, 6 parts of 2-butene-1,4-diol and 48 parts of dimethylformamide were mixed uniformly at 70°C, 4 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.1 parts of dibutyltin dilaurate were added, and the mixture was reacted at 120 rpm for 2 h. The mixture was cooled to 25°C at a rate of 5°C / min, and 5 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added dropwise at a rate of 1 mL / min. The mixture was reacted for 1 h. The solid was collected by filtration, washed 3 times with deionized water, and dried in an oven at 55°C for 10 h to obtain a modified polyurethane.

[0032] (5) 13 parts of modified polyurethane, 100 parts of dimethylformamide, and 25 parts of tetrahydrofuran were stirred at 30°C for 1 hour, and then transferred to the electrostatic spray assembly via a metering pump. The mixture was sprayed onto the surface of the hygroscopic and heat-generating fabric 15 cm away from the nozzle at a voltage of 10 kV and an injection speed of 0.5 mL / h. The fabric was then hot-pressed at a pressure of 1 MPa at 170°C for 2 minutes to obtain a waterproof multi-component composite fabric.

[0033] Example 2: (1) Under a nitrogen atmosphere, 5 parts of 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol, 20 parts of acrylonitrile, 0.2 parts of azobisisobutyronitrile, and 100 parts of dimethyl sulfoxide were mixed uniformly, heated to 60°C, stirred at 100 rpm for 13 h, 325 parts of methanol were added, stirred for 35 min, the solid was filtered, washed with methanol 3 times, and dried in an oven at 55°C for 16 h to obtain modified polyacrylonitrile;

[0034] (2) 10 parts of modified polyacrylonitrile and 120 parts of toluene were mixed evenly, 2 parts of a copper chloride-ethanol solution having a copper chloride content of 0.1 g / mL were added, and the mixture was stirred at 180 rpm for 50 min. The solid was collected and placed in an oven at 55° C. to dry for 16 h to obtain a composite modified polyacrylonitrile;

[0035] (3) drying the composite modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder at 90° C. for 1.5 h, transferring it into a spinning machine and melt-spinning it at 335° C., wherein the spinning pressure is 50 MPa, the humidity is 54%, and the spinning speed is 1200 m / min, then stretching it to 1.6 times at 285° C., curling it at 270° C., relaxing and shaping it at 270° C., stretching it to 0.9 times, cooling it at a cooling air temperature of 18° C., a wind speed of 0.9 m / s, and a wind pressure of 700 Pa, cooling it for 15 min, and weaving it into a fabric by interlacing the warp and weft to obtain a hygroscopic and heat-generating fabric; the mass ratio of the composite modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder is 20:1; the ratio of expanded graphite to hydrotalcite in the expanded graphite-hydrotalcite mixed powder is 1:2;

[0036] (4) Under a nitrogen atmosphere, 10 parts of 2-butene-1,4-diol and 77 parts of dimethylformamide were mixed uniformly at 75°C, 7 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.2 parts of dibutyltin dilaurate were added, and the mixture was reacted at 120 rpm for 4 h. The mixture was cooled to 30°C at a rate of 5°C / min, and 8 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added dropwise at a rate of 1 mL / min. The mixture was reacted for 2 h. The solid was collected by filtration, washed three times with deionized water, and dried in an oven at 60°C for 13 h to obtain a modified polyurethane.

[0037] (5) 22 parts of modified polyurethane, 170 parts of dimethylformamide, and 40 parts of tetrahydrofuran were stirred at 30°C for 1.5 hours, and then transferred to the electrostatic spray assembly via a metering pump. The mixture was sprayed onto the surface of the hygroscopic and heat-generating fabric 15 cm away from the nozzle at a voltage of 15 kV and an injection speed of 0.7 mL / h. The fabric was then hot-pressed at a pressure of 3 MPa at 170°C for 3 minutes to obtain a waterproof multi-component composite fabric.

[0038] Example 3: (1) Under a nitrogen atmosphere, 7 parts of 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol, 25 parts of acrylonitrile, 0.3 parts of azobisisobutyronitrile, and 125 parts of dimethyl sulfoxide were mixed uniformly, heated to 65°C, stirred at 100 rpm for 16 h, 400 parts of methanol were added, stirred for 45 min, the solid was filtered, washed with methanol 3 times, and dried in an oven at 60°C for 18 h to obtain modified polyacrylonitrile;

[0039] (2) 15 parts of modified polyacrylonitrile and 180 parts of toluene were mixed evenly, 3 parts of a copper chloride-ethanol solution having a copper chloride content of 0.1 g / mL were added, and the mixture was stirred at 180 rpm for 60 min. The solid was collected and placed in an oven at 60° C. to dry for 18 h to obtain a composite modified polyacrylonitrile;

[0040] (3) drying the composite modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder at 100° C. for 2 h, transferring it into a spinning machine for melt spinning at 340° C., wherein the spinning pressure is 60 MPa, the humidity is 60%, and the spinning speed is 1200 m / min, then stretching it to 2.5 times at 290° C., curling it at 280° C., relaxing and shaping it at 285° C., stretching it to 1.2 times, cooling it at a cooling air temperature of 22° C., a wind speed of 1.2 m / s, and a wind pressure of 800 Pa, cooling it for 20 min, and weaving it into a fabric by interlacing the warp and weft to obtain a hygroscopic and heat-generating fabric; the mass ratio of the composite modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder is 20:1; the ratio of expanded graphite to hydrotalcite in the expanded graphite-hydrotalcite mixed powder is 1:2;

[0041] (4) Under a nitrogen atmosphere, 14 parts of 2-butene-1,4-diol and 106 parts of dimethylformamide were mixed uniformly at 80° C., 10 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.3 parts of dibutyltin dilaurate were added, and the mixture was reacted at 120 rpm for 6 h. The mixture was cooled to 35° C. at a rate of 5° C. / min, and 11 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added dropwise at a rate of 1 mL / min. The mixture was reacted for 3 h. The solid was collected by filtration, washed three times with deionized water, and dried in an oven at 65° C. for 16 h to obtain a modified polyurethane.

[0042] (5) 31 parts of modified polyurethane, 240 parts of dimethylformamide, and 55 parts of tetrahydrofuran were stirred at 30°C for 2 h, and then transferred to the electrostatic spray assembly via a metering pump. The mixture was sprayed onto the surface of the hygroscopic and heat-generating fabric at a distance of 15 cm from the nozzle at a voltage of 20 kV and an injection speed of 0.9 mL / h. The fabric was then hot-pressed at a pressure of 5 MPa at 170°C for 4 min to obtain a waterproof multi-component composite fabric.

[0043] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (4) is different. Step (4) is changed to: Under a nitrogen atmosphere, 10 parts of 1,4-butanediol and 77 parts of dimethylformamide are mixed uniformly at 75°C, 7 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.2 parts of dibutyltin dilaurate are added, reacted at 120rpm for 4h, cooled to 30°C at 5°C / min, 8 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are added dropwise at a rate of 1mL / min, reacted for 2h, solids are collected by filtration, washed with deionized water 3 times, and dried in an oven at 60°C for 13h to obtain modified polyurethane. The remaining steps are the same as those in Example 2.

[0044] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (4) is different. Step (4) is changed to: Under a nitrogen atmosphere, 10 parts of 2-butene-1,4-diol and 77 parts of dimethylformamide are mixed uniformly at 75°C, 7 parts of 1,6-hexamethylene diisocyanate and 0.2 parts of dibutyltin dilaurate are added, reacted at 120rpm for 4h, cooled to 30°C at 5°C / min, 8 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are added dropwise at a rate of 1mL / min, reacted for 2h, solids are collected by filtration, washed with deionized water 3 times, and dried in an oven at 60°C for 13h to obtain modified polyurethane. The remaining steps are the same as those in Example 2.

[0045] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (4) is different. Step (4) is changed to: Under a nitrogen atmosphere, 10 parts of 2-butene-1,4-diol and 77 parts of dimethylformamide are mixed uniformly at 75°C, 7 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.2 parts of dibutyltin dilaurate are added, reacted at 120rpm for 4h, cooled to 30°C at 5°C / min, solids are collected by filtration, washed with deionized water 3 times, and dried in an oven at 60°C for 13h to obtain modified polyurethane. The remaining steps are the same as those in Example 2.

[0046] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (5) is different. Step (5) is changed to: 22 parts of modified polyurethane, 170 parts of dimethylformamide, and 40 parts of tetrahydrofuran are stirred at 30°C for 1.5 hours, conveyed to the spinning assembly through a metering pump, spun to the receiving plate at 50°C, and then introduced into the first stage coagulation bath, the coagulation bath uses an aqueous solution, coagulated for 1 minute, drawn to 1.4 times, washed with 85°C water, drawn to 0.8 times, then dried by a hot roller at 95°C for 0.5 minutes, drawn to 0.9 times, relaxed and fixed at 85°C, drawn to 0.8 times, then placed on the surface of a moisture-absorbing and heat-generating fabric, and then hot-pressed with a 170°C hot press at a pressure of 3MPa for 3 minutes to obtain a waterproof multi-component composite fabric. The remaining steps are the same as those of Example 2.

[0047] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (1), and step (2) is changed to: 10 parts of polyacrylonitrile with a molecular weight of 150,000 and 120 parts of toluene are mixed evenly, 2 parts of copper chloride-ethanol solution with a copper chloride content of 0.1 g / mL are added, and stirred at 180 rpm for 50 min, the solid is collected, and placed in an oven at 55° C. to dry for 16 h to obtain a composite modified polyacrylonitrile. The remaining steps are the same as in Example 2.

[0048] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that there is no step (2), and step (3) is changed to: the modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder are dried at 90°C for 1.5h, transferred to a spinning machine for melt spinning at 335°C, wherein the spinning pressure is 50MPa, the humidity is 54%, and the spinning speed is 1200m / min, then drawn to 1.6 times at 285°C, curled at 270°C, relaxed and shaped at 270°C, drawn to 0.9 times, with a cooling wind temperature of 18°C, a wind speed of 0.9m / s, and a wind pressure of 700Pa, cooled for 15min, and woven into a fabric by warp and weft interlacing to obtain a hygroscopic and heat-generating fabric; the mass ratio of the modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder is 20:1; the ratio of expanded graphite to hydrotalcite in the expanded graphite-hydrotalcite mixed powder is 1:2. The remaining steps are the same as in Example 2.

[0049] Comparative Example 7: The difference between Comparative Example 7 and Example 2 is that step (3) is different. Step (3) is changed to: the composite modified polyacrylonitrile is dried at 90°C for 1.5h, transferred to a spinning machine and melt-spun at 335°C, wherein the spinning pressure is 50MPa, the humidity is 54%, and the spinning speed is 1200m / min, then drawn to 1.6 times at 285°C, curled at 270°C, relaxed and shaped at 270°C, drawn to 0.9 times, cooled with a cooling air temperature of 18°C, a wind speed of 0.9m / s, and a wind pressure of 700Pa, cooled for 15min, and woven into a fabric by warp and weft interlacing to obtain a hygroscopic and heat-generating fabric. The remaining steps are the same as those in Example 2.

[0050] Effect example

[0051] Table 1 below shows the performance analysis results of the waterproof multi-component composite fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.

[0052] Table 1

[0053]

[0054] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Examples 1, 2, and 3, it can be found that the hydroxyl group of 2-butene-1,4-diol is combined with the isocyanate group in 1-chloromethyl-2,4-diisocyanobenzene and modified with 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane to obtain a modified polyurethane carrying a silane segment. The presence of the silane segment can optimize the elasticity and mechanical properties of the polyurethane protective layer, thereby indirectly improving the mechanical properties of the fabric. At the same time, the phenomenon of fabric aging caused by oxidation of copper ions in the hygroscopic and heat-generating fabric is reduced, achieving a long-lasting antibacterial effect, and the protective layer carries Some benzene rings, alkyl chains, silicon oxygen bonds and other hydrophobic groups can initially isolate bacteria from adhering, which is beneficial to the improvement of antibacterial effect and can also achieve the waterproof effect of the fabric; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that the modified polyurethane is deposited on the surface of the hygroscopic and heat-generating fabric by the electrostatic spray method, and breaks through the surface tension in the form of droplets under the action of the electric field force. When flying in the air, the solvent in the droplets evaporates to form a wrinkled microsphere structure, thereby improving the liquid repellency and further enhancing the waterproof performance. The active groups therein can be combined with the surface of the hygroscopic and heat-generating fabric by chemical bonds under the action of electrostatics, and then on the surface A stable and firm protective layer is formed on the surface of the material; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol participates in the polymerization reaction of polyacrylonitrile to form a cross-linked network structure, which significantly improves the mechanical strength of the fabric, assists the sulfur element, and further improves the antibacterial performance. At the same time, the presence of hydroxyl groups can increase the hydrophilicity of the fabric, thereby enhancing the moisture absorption effect; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6, it can be found that after coordination with copper chloride, the copper ions therein can destroy the outer cell membrane of bacteria and disrupt the bacterial The internal current of bacteria is prevented from regenerating bacteria, thereby achieving the antibacterial effect. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 7, it can be found that the expanded graphite-hydrotalcite mixture can gather and compress trace gases, so that the fiber has a honeycomb microporous structure, and the specific surface area of ​​the fiber is increased, thereby enhancing the capillary action of the fiber and improving the hygroscopicity. At the same time, the enhancement of hygroscopicity enables the fiber to absorb water molecules in the air, converting them from gaseous state to liquid state, and liquefying to generate heat, thereby achieving the heating effect. On this basis, there are many irregular pores in the honeycomb structure, which increases the extensibility of the fiber and improves the tensile strength of the fiber.

[0055] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a waterproof multi-component composite fabric, characterized in that: The method comprises the following preparation steps: (1) 5 to 15 parts of modified polyacrylonitrile and 60 to 180 parts of toluene are uniformly mixed, 1 to 3 parts of copper chloride-ethanol solution are added, and the mixture is stirred at 180 rpm for 40 to 60 minutes. The solid is collected and placed in an oven at 50 to 60° C. to dry for 14 to 18 hours to obtain a composite modified polyacrylonitrile; (2) drying the composite modified polyacrylonitrile and expanded graphite-hydrotalcite mixed powder at 80-100° C. for 1-2 hours, transferring it into a spinning machine for melt spinning at 330-340° C., then drawing it to 0.7-2.5 times at 280-290° C., curling it at 260-280° C., relaxing and shaping it at 255-285° C., drawing it to 0.6-1.2 times, cooling it at a temperature of 14-22° C., a wind speed of 0.6-1.2 m / s, and a wind pressure of 600-800 Pa, cooling it for 10-20 minutes, and weaving it into a fabric by warp and weft interlacing to obtain a moisture-absorbing and heat-generating fabric; (3) Under a nitrogen atmosphere, 6 to 14 parts of 2-butene-1,4-diol and 48 to 106 parts of dimethylformamide were mixed uniformly at 70 to 80° C., 4 to 10 parts of 1-chloromethyl-2,4-diisocyanobenzene and 0.1 to 0.3 parts of dibutyltin dilaurate were added, and the mixture was reacted at 120 rpm for 2 to 6 hours, and the temperature was lowered to 25 to 35° C., and 5 to 11 parts of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane were added dropwise at a rate of 1 mL / min, and the mixture was reacted for 1 to 3 hours. The solid was collected by filtration, washed with deionized water for 3 times, and dried in an oven at 55 to 65° C. for 10 to 16 hours to obtain a modified polyurethane; (4) 13 to 31 parts of modified polyurethane, 100 to 240 parts of dimethylformamide, and 25 to 55 parts of tetrahydrofuran are stirred at 30°C for 1 to 2 hours, and then conveyed to an electrostatic spray assembly via a metering pump and sprayed onto the surface of a hygroscopic and heat-generating fabric 15 cm away from the nozzle. The fabric is then heat-pressed with a heat press for 2 to 4 minutes to obtain a waterproof multi-component composite fabric.

2. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The preparation step of the modified polyacrylonitrile in step (1) is as follows: in a nitrogen atmosphere, 3 to 7 parts of 4-(1-amino-3-methylsulfonyl-propyl)-1,6-heptadien-4-ol, 15 to 25 parts of acrylonitrile, 0.1 to 0.3 parts of azobisisobutyronitrile, and 75 to 125 parts of dimethyl sulfoxide are mixed uniformly, the temperature is raised to 55 to 65° C., and the mixture is stirred at 100 rpm for 10 to 16 hours. 250 to 400 parts of methanol are added, and the mixture is stirred for 25 to 45 minutes. The solid is filtered and washed with methanol for 3 times, and dried in an oven at 50 to 60° C. for 14 to 18 hours to obtain the modified polyacrylonitrile.

3. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The content of copper chloride in the copper chloride-ethanol solution in step (1) is 0.1 g / mL.

4. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The mass ratio of the composite modified polyacrylonitrile to the expanded graphite-hydrotalcite mixed powder in step (2) is 20:

1.

5. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: In step (2), the ratio of expanded graphite to hydrotalcite in the expanded graphite-hydrotalcite mixed powder is 1:

2.

6. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The parameters of the spinning machine in step (2) are: spinning pressure 40-60 MPa, humidity 48-60%, and spinning speed 1200 m / min.

7. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The cooling rate in step (3) is 5°C / min.

8. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The parameters of the electrostatic spray assembly in step (4) are voltage 10-20 kV and injection speed 0.5-0.9 mL / h.

9. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The temperature of the hot press in step (4) is 170°C.

10. The method for preparing a waterproof multi-component composite fabric according to claim 1, characterized in that: The pressure of the hot press in step (4) is 1 to 5 MPa.